The Ankyrin-Repeat Gene GmANK114 Confers Drought and Salt Tolerance in Arabidopsis and Soybean - Zhao, Juan-Ying; Lu, Zhi-Wei; Sun, Yue; Fang, Zheng-Wu; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Xu, Zhao-Shi; Min, Dong-Hong (Frontiers in Plant Science, 2020)
Ankyrin repeat (ANK) proteins are essential in cell growth, development and response to hormones and environmental stresses. In the present study, 226 ANK genes were identified and classified into nine subfamilies according to conserved domains in the soybean genome (Glycine max L.). Among them, the GmANK114 was highly induced by drought, salt, and abscisic acid (ABA). The GmANK114 encodes a protein that belongs to the ANK-RF subfamily containing a RING finger (RF) domain in addition to the ankyrin repeats. Heterologous overexpression of GmANK114 in transgenic Arabidopsis improved the germination rate under drought and salt treatments compared to WT. Homologous overexpression of GmANK114 improved the survival rate under drought and salt stresses in transgenic soybean hairy roots. In response to drought or salt stress, GmANK114 overexpression in soybean hairy root showed higher proline (Pro) and lower malondialdehyde (MDA) contents, and lower H2O2 and O2- contents compared control plants. Besides, GmANK114 activated transcription of several abiotic stress-related genes, including WRKY13, NAC11, DREB2, MYB84, and bZIP44 under drought and salt stresses in soybean. These results provide new insights for functional analysis of soybean ANK proteins and will be helpful for further understanding how ANK proteins in plants adapt to abiotic stress.